Peran Guru dan Pengelolaan Pojok Baca Kelas dalam Meningkatkan Literasi PAI Peserta Didik di SD Muhammadiyah Mentok - Rica Khoirany (4, 2025)
Low literacy skills lead to low reading interest among elementary school students. This low reading interest results in low cognitive and intellectual abilities. Teachers are tasked and responsible for guiding and shaping students' literacy behavior, thereby achieving the goals of the School Literacy Movement. This study aims to analyze the role of teachers in improving Islamic Religious Education literacy in students at Muhammadiyah Mentok Elementary School and the management of classroom reading corners in improving Islamic Religious Education literacy in students at Muhammadiyah Mentok Elementary School. This study used a qualitative approach with a field study. The subjects were the principal and teachers of Muhammadiyah Mentok Elementary School. Data were collected through observation, interviews, and documentation, then analyzed using data reduction, data presentation, and conclusion drawing techniques. The results of the study indicate that: First, the role of teachers in improving Islamic Religious Education literacy in students at Muhammadiyah Mentok Elementary School has been well-functioning, as educators, instructors, inspirators, motivators, innovators, facilitators, demonstrators, class managers, mediators, and evaluators. Second, the management of the class reading corner in improving the Islamic Religious Education literacy of students at Muhammadiyah Mentok Elementary School has been appropriate, including planning, organizing, directing, and controlling. Abstrak Rendahnya kemampuan literasi menyebabkan rendahnya minat baca di kalangan peserta didik sekolah dasar. Rendahnya minat baca tersebut mengakibatkan rendahnya kemampuan kognitif dan intelektual peserta didik Guru bertugas dan bertanggung jawab untuk mengarahkan dan membentuk perilaku literasi peserta didik, sehingga tujuan dari Gerakan Literasi Sekolah itu sendiri dapat tercapai. Penelitian bertujuan untuk menganalisis peran guru dalam meningkatkan literasi PAI peserta didik di SD Muhammadiyah Mentok, dan menganalisis pengelolaan pojok baca kelas dalam meningkatkan literasi PAI peserta didik di SD Muhammadiyah Mentok. Penelitian ini menggunakan pendekatan kualitatif dengan jenis penelitian studi lapangan (field reseacrh). Subjek penelitian adalah kepsek beserta guru SD Muhammadiyah Mentok. Data dikumpulkan melalui observasi, wawancara, dan dokumentasi, kemudian dianalisis dengan teknik reduksi data, penyajian data, dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa: Pertama, peran guru dalam meningkatkan literasi PAI peserta didik di SD Muhammadiyah Mentok telah berjalan dengan baik yaitu sebagai pendidik, pengajar, inspirator, motivator, inovator, fasilitator, demonstrator, pengelola kelas, mediator, dan evaluator. Kedua, pengelolaan pojok baca kelas dalam meningkatkan literasi PAI peserta didik di SD Muhammadiyah Mentok telah sesuai yang meliputi planning, organizing, directing, dan controlling.